Embedding employability within higher education for the profession of policing. Issue 3 (12th August 2019) - Pepper, Ian; McGrath, Ruth
Abstract : Purpose: The purpose of this paper is to evaluate the impact of an employability module, the College of Policing Certificate in Knowledge of Policing (CKP), on students' career aspirations, their confidence and wish to join the police along with the appropriateness of the module. This will inform the implementation of employability as part of the College of Policing-managed Police Education Qualifications Framework (PEQF). Design/methodology/approach: A three-year longitudinal research study used mixed methods across four points in time to evaluate the impact on students studying the employability module. Findings: The research suggests that the employability-focussed CKP was useful as an introduction to policing, it developed interest in the police and enhanced the confidence of learners applying to join. Lessons learnt from the CKP should be considered during the implementation of the PEQF. Research limitations/implications: The ability to generalise findings across different groups is limited as other influences may impact on a learner's confidence and employability. However, the implications for the PEQF curriculum are worthy of consideration. Practical implications: As the police service moves towards standardised higher educational provision and evolution of policing as a profession, lessons can be learnt from the CKP with regards to the future employability of graduates. Originality/value: Enhancing the employability evidence base, focussing on policing, the research identified aspects which may impact on graduates completing a degree mapped to the PEQF. The research is therefore of value to higher education and the professional body for policing.